2014
DOI: 10.3163/1536-5050.102.1.008
|View full text |Cite
|
Sign up to set email alerts
|

Providing an information prescription in veterinary medical clinics: a pilot study

Abstract: The value placed on reliable Internet information by veterinary clients suggests several opportunities for librarians to become more proactive in partnering with veterinarians to facilitate the education of pet owners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 8 publications
2
23
0
Order By: Relevance
“…Although the practice of guiding clients to Internet sites is widely common in veterinary services, only few studies have examined the impact of this intervention. In previous studies, the impact of two types of information prescriptions (indirect (generic) Info RX and, direct (topic specific) Info RX) has been examined on client relations and clinic success (Kogan, Schoenfeld‐Tacher, Gould, Viera, et al., ; Kogan, Schoenfeld‐Tacher, Gould, Hellyer, et al., ; Solhjoo, ). The findings of these studies clearly illustrate the positive reactions reported by pet owners when given an information prescription.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the practice of guiding clients to Internet sites is widely common in veterinary services, only few studies have examined the impact of this intervention. In previous studies, the impact of two types of information prescriptions (indirect (generic) Info RX and, direct (topic specific) Info RX) has been examined on client relations and clinic success (Kogan, Schoenfeld‐Tacher, Gould, Viera, et al., ; Kogan, Schoenfeld‐Tacher, Gould, Hellyer, et al., ; Solhjoo, ). The findings of these studies clearly illustrate the positive reactions reported by pet owners when given an information prescription.…”
Section: Resultsmentioning
confidence: 99%
“…There were only three studies about pet health information interventions, of which two of them assessed outcomes of vet's information prescription using self‐report questionnaires to measure online information use, trust in online health information and self‐efficacy for information seeking. Participants were asked about the number of times they had used the information prescription to access pet health related information and what their plans were for utilising the information they found online over the previous 2 months (Kogan, Schoenfeld‐Tacher, Gould, Viera, et al., ; Kogan, Schoenfeld‐Tacher, Gould, Hellyer, et al., ). In another study about veterinarian's information prescriptions, pet owners were asked to self‐report their outcomes qualitatively by means of open questions (Solhjoo, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations